Multifunctional composite coating diaphragm and preparation method thereof
By using a multifunctional composite coating separator on the lithium-ion battery separator, combining polyolefin-based film, ceramic slurry and electrospinning layer, the traditional separator has solved the shortcomings in heat resistance and conductivity, and a high-performance battery separator is achieved.
Patent Information
- Application Number
- CN202411486296.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Traditional lithium-ion battery separators have shortcomings in heat resistance, mechanical strength and electrolyte permeability, which are difficult to meet the needs of high energy density and high safety batteries.
The multifunctional composite coating membrane is used, including polyolefin-based film, ceramic slurry coating and electrospinning layer. The raw materials of the electrospinning layer include aramid and polymethyl methacrylate. The ceramic powder is modified and prepared by a combination of microgravure coating, electrospinning and hot rolling.
It significantly improves the heat resistance, mechanical strength and ionic conductivity of the battery separator, achieves excellent performance of various properties, and provides guarantee for the performance improvement of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a multifunctional composite coating separator and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy industry, lithium-ion batteries, as important energy storage devices, have become a hot topic in research. As one of the key components of lithium-ion batteries, the diaphragm directly affects the safety, energy density and cycle life of the battery. Traditional diaphragm materials have deficiencies in heat resistance, mechanical strength and electrolyte permeability, making it difficult to meet the needs of high energy density and high safety batteries.
[0003] In recent years, improving the performance of diaphragms through surface coating technology has become an important research direction. However, a single coating material is often difficult to meet multiple performance requirements at the same time. Therefore, it is particularly important to develop a composite coating diaphragm that integrates multiple excellent properties. Summary of the invention
[0004] The present invention provides a multifunctional composite coating diaphragm and a preparation method thereof, which solves the problems of single coating, poor heat resistance and low ion conductivity of battery diaphragms in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a multifunctional composite coating diaphragm, which comprises a polyolefin base film, a ceramic slurry coating, and an electrospinning layer in order from top to bottom; The raw material of the electrospinning layer includes a polymer; The polymer comprises aramid and polymethyl methacrylate in a mass ratio of 5:1-9.
[0006] As a further technical solution, the mass ratio of the aramid fiber to polymethyl methacrylate is 5:3-7.
[0007] In the present invention, when the mass ratio of aramid to polymethyl methacrylate is 5:3-7, the heat resistance of the battery separator is further improved.
[0008] As a further technical solution, the raw materials of the ceramic slurry coating include ceramic powder; The particle size D50 of the ceramic powder is 0.2-0.8 μm; The ceramic powder includes one or more of alumina, SiO2, and boehmite.
[0009] As a further technical solution, the ceramic powder is a modified ceramic powder, and the preparation method of the modified ceramic powder comprises the following steps: mixing 2-ethyl formate benzenesulfonamide solution and ceramic powder, and drying to obtain the modified ceramic powder.
[0010] As a further technical solution, the 2-ethylformate benzenesulfonamide solution is a mixture of 2-ethylformate benzenesulfonamide and ethanol; the mass volume ratio of the 2-ethylformate benzenesulfonamide and ethanol is 1g:60~70mL; the mass ratio of the 2-ethylformate benzenesulfonamide and ceramic powder is 1:8~10.
[0011] In the present invention, 2-ethyl formate benzenesulfonamide solution is used and ceramic powder is modified to further improve the heat resistance of the battery separator.
[0012] As a further technical solution, the polyolefin-based film is a polyethylene-based film or a polypropylene-based film.
[0013] As a further technical solution, the thickness of the polyolefin base film is 5-10 μm; the thickness of the ceramic slurry coating is 1-2 μm; and the thickness of the electrospinning layer is 2-3 μm.
[0014] As a further technical solution, the raw material of the electrospinning layer also includes carbon-coated zirconium phosphate; the mass ratio of the carbon-coated zirconium phosphate to the polymer is 1:7-9.
[0015] As a further technical solution, the preparation method of the carbon-coated zirconium phosphate comprises the following steps: mixing an organic carbon source, a solvent, and zirconium phosphate, and calcining to obtain the carbon-coated zirconium phosphate; The mass ratio of the organic carbon source, zirconium phosphate and solvent is 1-2:10:35; The organic carbon source includes starch; the solvent includes water; The calcination temperature is 300-400° C. and the calcination time is 20-30 minutes.
[0016] In the present invention, after the carbon-coated zirconium phosphate and other components are added to the electrospinning layer to prepare the electrospinning layer, the heat resistance and ion conductivity of the battery separator are further improved.
[0017] The present invention also provides a method for preparing the multifunctional composite coating membrane, comprising the following steps: S1, mixing ceramic powder and binder solution to obtain a ceramic slurry with a solid content of 30wt% to 45wt%; S2, mixing the raw material of the electrospinning layer and the solvent to obtain an electrospinning solution with a solid content of 2wt% to 10wt%; S3, coating the ceramic slurry on the surface of the polyolefin base film, and drying to obtain a ceramic slurry coating base film; S4, electrospinning the electrospinning solution onto the ceramic slurry coating of the ceramic slurry coating base membrane, and hot rolling to obtain a multifunctional composite coating diaphragm.
[0018] As a further technical solution, the components of the binder solution include a binder, a dispersant and water; the mass ratio of the ceramic powder, the binder and the dispersant is 30:1:0.1~0.3; The binder includes one of polyvinyl alcohol and polyacrylamide; the dispersant includes one or more of polyacrylic acid, sodium polyacrylate and hydroxymethyl cellulose.
[0019] As a further technical solution, in step S2, the solvent includes one of DMF and DMSO; In step S3, the coating method includes micro-gravure coating.
[0020] As a further technical solution, the temperature of the hot roller pressing is 20-150°C, preferably 30-100°C, more preferably 50-80°C; The pressure of the hot roller pressing compound is 5 to 80 psi, preferably 10 to 60 psi, more preferably 20 to 50 psi; The voltage of the electrostatic spinning is 20-30 kV, and the spinning distance is 6-10 cm.
[0021] In the present invention, a composite coating diaphragm is successfully prepared by combining micro-gravure roller coating, electrostatic spinning and hot roller pressing, which combines the heat resistance of ceramic inorganic coating and the high mechanical strength and strong adhesion of electrostatically spun polymer aromatics. This composite coating diaphragm has excellent performance in various properties, providing a strong guarantee for the performance improvement of lithium-ion batteries.
[0022] In the hot roller lamination process, the present invention precisely controls the temperature and pressure. By optimizing the temperature and pressure range of the hot roller lamination, a good combination between the coating and the substrate is ensured, while the damage to the diaphragm substrate by high temperature and high pressure is avoided. This optimized process not only improves production efficiency, but also ensures the stability and consistency of the product.
[0023] The working principle and beneficial effects of the present invention are: In the present invention, a ceramic slurry coating and an electrospinning layer are sequentially coated on the surface of a polyolefin base film to achieve a perfect composite of an inorganic coating and an organic coating, thereby forming a multifunctional composite coating diaphragm with excellent heat resistance, high mechanical strength, good adhesion and high-efficiency ion transmission performance. By combining the micron-scale pores of the electrospinning layer and the nanoscale pores of the ceramic slurry, a gradient pore structure is constructed on the surface of the diaphragm, and the pore size is gradually reduced from the surface to the inside of the diaphragm. This design not only improves the permeability of the electrolyte, allowing the electrolyte to penetrate into the inside of the diaphragm more quickly and evenly, but also optimizes the ion transmission path and significantly improves the ion transmission efficiency; and the polymer of the electrospinning layer is a combination of aramid and polymethyl methacrylate, which significantly improves the heat resistance and ion conductivity of the diaphragm. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the following examples and comparative examples, The model of polyvinyl alcohol is 2099; the weight average molecular weight of polymethyl methacrylate is 30,000; the weight average molecular weight of aramid is 50,000; Polyethylene-based film: It is obtained by mixing polyethylene with a molecular weight of 500,000 and white oil and extruding the mixture into a film; the mass ratio of polyethylene to white oil is 2:8.
[0026] Example 1 The multifunctional composite coating membrane includes, from top to bottom, a polyethylene-based film (9 μm thick), a ceramic slurry coating (1.5 μm), and an electrospinning layer (2.5 μm); The preparation method of the multifunctional composite coating diaphragm comprises the following steps: S1, polyvinyl alcohol, hydroxymethyl cellulose and water are mixed to obtain a binder solution, and alumina (particle size D50 is 0.5 μm) is added and continued to mix to obtain a ceramic slurry with a solid content of 40 wt%; Among them, the mass ratio of aluminum oxide, polyvinyl alcohol and hydroxymethyl cellulose is 30:1:0.2; S2, mixing aramid, polymethyl methacrylate and DMF to obtain an electrospinning solution with a solid content of 8 wt%; Among them, the mass ratio of aramid and polymethyl methacrylate is 5:2; S3, micro-gravure coating ceramic slurry on the upper surface of the polyethylene base film, and drying to obtain a ceramic slurry coating base film; S4. Electrospinning the electrospinning liquid onto the ceramic slurry coating of the ceramic slurry coating base membrane, and hot rolling at 50° C. and 50 psi to obtain a multifunctional composite coating diaphragm; wherein the electrospinning voltage is 25 kV and the spinning distance is 8 cm.
[0027] Example 2 The multifunctional composite coating membrane includes, from top to bottom, a polyethylene-based film (9 μm thick), a ceramic slurry coating (1.5 μm), and an electrospinning layer (2.5 μm); The preparation method of the multifunctional composite coating diaphragm comprises the following steps: S1, mixing polyacrylamide, hydroxymethyl cellulose and water to obtain a binder solution, adding boehmite (particle size D50 is 0.8 μm) and continuing to mix to obtain a ceramic slurry with a solid content of 45 wt%; Among them, the mass ratio of boehmite, polyvinyl alcohol and hydroxymethyl cellulose is 30:1:0.3; S2, mixing aramid, polymethyl methacrylate and DMSO to obtain an electrospinning solution with a solid content of 10 wt%; Among them, the mass ratio of aramid and polymethyl methacrylate is 5:9; S3, micro-gravure coating ceramic slurry on the upper surface of the polyethylene base film, and drying to obtain a ceramic slurry coating base film; S4. Electrospinning the electrospinning liquid onto the ceramic slurry coating of the ceramic slurry coating base membrane, and hot rolling at 150° C. and 5 psi to obtain a multifunctional composite coating diaphragm; wherein the electrospinning voltage is 30 kV and the spinning distance is 10 cm.
[0028] Example 3 The multifunctional composite coating membrane includes, from top to bottom, a polyethylene-based film (9 μm thick), a ceramic slurry coating (1.5 μm), and an electrospinning layer (2.5 μm); The preparation method of the multifunctional composite coating diaphragm comprises the following steps: S1, polyvinyl alcohol, sodium polyacrylate and water are mixed to obtain a binder solution, SiO2 (particle size D50 is 0.2 μm) is added and continued to mix to obtain a ceramic slurry with a solid content of 30 wt%; Among them, the mass ratio of SiO2, polyvinyl alcohol and sodium polyacrylate is 30:1:0.1; S2, mixing aramid, polymethyl methacrylate and DMF to obtain an electrospinning solution with a solid content of 2 wt%; Among them, the mass ratio of aramid and polymethyl methacrylate is 5:1; S3, micro-gravure coating ceramic slurry on the upper surface of the polyethylene base film, and drying to obtain a ceramic slurry coating base film; S4. Electrospinning the electrospinning liquid onto the ceramic slurry coating of the ceramic slurry coating base membrane, and hot rolling at 20° C. and 80 psi to obtain a multifunctional composite coating diaphragm; wherein the electrospinning voltage is 20 kV and the spinning distance is 6 cm.
[0029] Example 4 The only difference between this embodiment and embodiment 1 is that the mass ratio of aramid fiber to polymethyl methacrylate is 5:8.
[0030] Example 5 The only difference between this embodiment and embodiment 1 is that the mass ratio of aramid fiber to polymethyl methacrylate is 5:7.
[0031] Example 6 The only difference between this embodiment and embodiment 1 is that the mass ratio of aramid fiber to polymethyl methacrylate is 5:3.
[0032] Example 7 The only difference between this embodiment and embodiment 6 is that the alumina is modified alumina; The preparation method of modified alumina comprises the following steps: mixing 2-ethyl formate benzenesulfonamide and ethanol with a volume fraction of 70%, adding alumina, continuing to mix, and drying to obtain modified alumina; The mass volume ratio of 2-ethylformate benzenesulfonamide to ethanol is 1 g:60 mL; the mass ratio of 2-ethylformate benzenesulfonamide to aluminum oxide is 1:10.
[0033] Example 8 The only difference between this embodiment and embodiment 6 is that the alumina is modified alumina; The preparation method of modified alumina comprises the following steps: mixing 2-ethyl formate benzenesulfonamide and ethanol with a volume fraction of 70%, adding alumina, continuing to mix, and drying to obtain modified alumina; The mass volume ratio of 2-ethylformate benzenesulfonamide and ethanol is 1 g:70 mL; the mass ratio of 2-ethylformate benzenesulfonamide and alumina is 1:8.
[0034] Example 9 The only difference between this embodiment and embodiment 8 is that the raw material of the electrospinning layer also includes carbon-coated zirconium phosphate; The preparation method of carbon-coated zirconium phosphate comprises the following steps: starch, water and zirconium phosphate are mixed, and calcined at 300° C. for 30 minutes to obtain carbon-coated zirconium phosphate; wherein the mass ratio of starch, zirconium phosphate and water is 1:10:35; Step S2 of the preparation method of the multifunctional composite coating diaphragm is: mixing aramid, polymethyl methacrylate, carbon-coated zirconium phosphate and DMF to obtain an electrospinning solution with a solid content of 8wt%; wherein the mass ratio of aramid to polymethyl methacrylate is 5:3, and the mass ratio of the sum of the mass of aramid and polymethyl methacrylate to the mass ratio of the carbon-coated zirconium phosphate is 9:1.
[0035] Example 10 The only difference between this embodiment and embodiment 8 is that the raw material of the electrospinning layer also includes carbon-coated zirconium phosphate; The preparation method of carbon-coated zirconium phosphate comprises the following steps: starch, water and zirconium phosphate are mixed, and calcined at 400° C. for 20 minutes to obtain carbon-coated zirconium phosphate; wherein the mass ratio of starch, zirconium phosphate and water is 2:10:35; Step S2 of the preparation method of the multifunctional composite coating diaphragm is: mixing aramid, polymethyl methacrylate, carbon-coated zirconium phosphate and DMF to obtain an electrospinning solution with a solid content of 8wt%; wherein the mass ratio of aramid to polymethyl methacrylate is 5:3, and the mass ratio of the sum of the mass of aramid and polymethyl methacrylate to the mass ratio of the carbon-coated zirconium phosphate is 7:1.
[0036] Comparative Example 1 The multifunctional composite coating diaphragm includes a polyethylene-based film (9 μm thick) and a ceramic slurry coating (1.5 μm) from top to bottom. The preparation method of the multifunctional composite coating diaphragm comprises the following steps: S1, polyvinyl alcohol, hydroxymethyl cellulose and water are mixed to obtain a binder solution, and alumina (particle size D50 is 0.5 μm) is added and continued to mix to obtain a ceramic slurry with a solid content of 40 wt%; Among them, the mass ratio of aluminum oxide, polyvinyl alcohol and hydroxymethyl cellulose is 30:1:0.2; S2, mixing aramid, polymethyl methacrylate and DMF to obtain an electrospinning solution with a solid content of 8 wt%; Among them, the mass ratio of aramid and polymethyl methacrylate is 5:2; S3. Micro-gravure coating of ceramic slurry on the surface of the polyethylene base film, and drying to obtain a multifunctional composite coating diaphragm.
[0037] Comparative Example 2 The multifunctional composite coating diaphragm includes a polyethylene-based film (9 μm thick) and a ceramic slurry coating (1.5 μm) from top to bottom. The preparation method of the multifunctional composite coating diaphragm comprises the following steps: S1, mixing polyacrylamide, hydroxymethyl cellulose and water to obtain a binder solution, adding boehmite (particle size D50 is 0.8 μm) and continuing to mix to obtain a ceramic slurry with a solid content of 45 wt%; Among them, the mass ratio of boehmite, polyvinyl alcohol and hydroxymethyl cellulose is 30:1:0.3; S2, mixing aramid, polymethyl methacrylate and DMSO to obtain an electrospinning solution with a solid content of 10 wt%; Among them, the mass ratio of aramid and polymethyl methacrylate is 5:9; S3. Micro-gravure coating of ceramic slurry on the surface of the polyethylene base film, and drying to obtain a multifunctional composite coating diaphragm.
[0038] Comparative Example 3 The multifunctional composite coating diaphragm includes a polyethylene-based film (9 μm thick) and a ceramic slurry coating (1.5 μm) from top to bottom. The preparation method of the multifunctional composite coating diaphragm comprises the following steps: S1, polyvinyl alcohol, sodium polyacrylate and water are mixed to obtain a binder solution, SiO2 (particle size D50 is 0.2 μm) is added and continued to mix to obtain a ceramic slurry with a solid content of 30 wt%; Among them, the mass ratio of SiO2, polyvinyl alcohol and sodium polyacrylate is 30:1:0.1; S2, mixing aramid, polymethyl methacrylate and DMF to obtain an electrospinning solution with a solid content of 2 wt%; Among them, the mass ratio of aramid and polymethyl methacrylate is 5:1; S3. Micro-gravure coating of ceramic slurry on the surface of the polyethylene base film, and drying to obtain a multifunctional composite coating diaphragm.
[0039] Comparative Example 4 The difference between this comparative example and Example 1 is that aramid is replaced by polymethyl methacrylate.
[0040] Comparative Example 5 The difference between this comparative example and Example 1 is that polymethyl methacrylate is replaced by aramid.
[0041] The heat resistance test was performed on the multifunctional composite coating membranes prepared in Examples 1 to 10 and Comparative Examples 1 to 5 respectively: The ionic conductivity test was performed on the multifunctional composite coating membranes prepared in Examples 1 to 3, Examples 8 to 10 and Comparative Examples 1 to 3 respectively; Heat resistance: After covering the top and bottom of the multifunctional composite coating separator with a piece of A4 paper, place it in an oven at 150°C for 1 hour, and then measure the transverse (TD) shrinkage and longitudinal (MD) shrinkage of the battery separator; Ionic conductivity: The AC impedance of the multifunctional composite coating membrane was tested using an electrochemical workstation. The ionic conductivity of the membrane was calculated based on the impedance. Five samples were tested and the results were averaged.
[0042] The results are shown in Tables 1~2 below.
[0043] Table 1 Test results of heat resistance of multifunctional composite coating diaphragm
[0044] Table 2 Test results of ionic conductivity of multifunctional composite coating membrane
[0045] Compared with Comparative Examples 1 to 5, the multifunctional composite coating membranes prepared in Examples 1 to 10 have higher ionic conductivity and lower shrinkage, indicating that the ceramic slurry coating and the electrospinning layer are sequentially coated on the surface of the polyolefin base membrane to achieve the composite of the inorganic coating and the organic coating, and the polymer of the electrospinning layer is a combination of aramid and polymethyl methacrylate, which significantly improves the heat resistance and ionic conductivity of the battery separator.
[0046] Compared with Examples 1 and 4, the shrinkage rate of the multifunctional composite coating separator prepared in Examples 5-6 is lower, indicating that when the mass ratio of aramid and polymethyl methacrylate is 5:3-7, the heat resistance of the battery separator is further improved.
[0047] Compared with Example 6, the shrinkage rate of the multifunctional composite coating separator prepared in Examples 7-8 is lower, indicating that the use of 2-ethylformate benzenesulfonamide solution and the modification of the ceramic powder further improve the heat resistance of the battery separator.
[0048] Compared with Example 8, the multifunctional composite coating membranes prepared in Examples 9 to 10 have higher ionic conductivity and lower shrinkage, indicating that after adding carbon-coated zirconium phosphate and other components to the electrospinning layer to prepare the electrospinning layer, the heat resistance and ionic conductivity of the battery membrane are further improved.
[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A multifunctional composite coating diaphragm, characterized in that: From top to bottom, it includes a polyolefin base film, a ceramic slurry coating, and an electrospinning layer; The raw material of the electrospinning layer includes a polymer; The polymer comprises aramid and polymethyl methacrylate in a mass ratio of 5:1-9.
2. A multifunctional composite coating diaphragm according to claim 1, characterized in that: The mass ratio of the aramid fiber to the polymethyl methacrylate is 5:3-7.
3. The multifunctional composite coating diaphragm according to claim 1, characterized in that: The raw materials of the ceramic slurry coating include ceramic powder; The particle size D50 of the ceramic powder is 0.2-0.8 μm; The ceramic powder includes one or more of alumina, SiO2, and boehmite.
4. A multifunctional composite coating diaphragm according to claim 3, characterized in that: The ceramic powder is a modified ceramic powder. The preparation method of the modified ceramic powder comprises the following steps: mixing 2-ethyl formate benzenesulfonamide solution and ceramic powder, and drying to obtain the modified ceramic powder.
5. The multifunctional composite coating diaphragm according to claim 1, characterized in that: The polyolefin-based film is a polyethylene-based film or a polypropylene-based film.
6. The multifunctional composite coating diaphragm according to claim 1, characterized in that: The thickness of the polyolefin-based film is 5-10 μm; the thickness of the ceramic slurry coating is 1-2 μm; and the thickness of the electrostatic spinning layer is 2-3 μm.
7. The multifunctional composite coating diaphragm according to claim 1, characterized in that: The raw material of the electrospinning layer also includes carbon-coated zirconium phosphate; the mass ratio of the carbon-coated zirconium phosphate to the polymer is 1:7-9.
8. The multifunctional composite coating membrane according to claim 7, characterized in that: The preparation method of the carbon-coated zirconium phosphate comprises the following steps: mixing an organic carbon source, a solvent and zirconium phosphate, and calcining to obtain the carbon-coated zirconium phosphate; The mass ratio of the organic carbon source, zirconium phosphate and solvent is 1-2:10:35; The calcination temperature is 300-400° C. and the calcination time is 20-30 minutes.
9. The method for preparing a multifunctional composite coating membrane according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing ceramic powder and binder solution to obtain a ceramic slurry with a solid content of 30wt% to 45wt%; S2, mixing the raw material of the electrospinning layer and the solvent to obtain an electrospinning solution with a solid content of 2wt% to 10wt%; S3, coating the ceramic slurry on the surface of the polyolefin base film, and drying to obtain a ceramic slurry coating base film; S4, electrospinning the electrospinning solution onto the ceramic slurry coating of the ceramic slurry coating base membrane, and hot rolling to obtain a multifunctional composite coating diaphragm.
10. The method for preparing a multifunctional composite coating membrane according to claim 9, characterized in that: The temperature of the hot roller pressing is 20-150°C, preferably 30-100°C, more preferably 50-80°C; The pressure of the hot roller pressing compound is 5 to 80 psi, preferably 10 to 60 psi, more preferably 20 to 50 psi; The voltage of the electrostatic spinning is 20-30 kV, and the spinning distance is 6-10 cm.
Citation Information
Patent Citations
Composite lithium ion battery ceramic diaphragm and preparation method thereof
CN104681764A
Separator for lithium ion secondary battery, and lithium metal battery comprising same
CN110622338A
Sol coating diaphragm and preparation method thereof
CN112072047A
Coating slurry for lithium battery diaphragm and coating process
CN113517517A